Lysossomal Membrane Stability of the brown mussel Perna perna (Linnaeus) (Mollusca, Bivalvia) exposed to the anionic surfactant Linear Alkylbenzene Sulphonate (LAS) - Stefanoni, Marina F. [UNESP]; Abessa, Denis M. S. [UNESP] (My University, 2008)
The effects of the Linear Alkylbenzene Sulphonate (LAS) were evaluated on the mussel Perna perna (Linnaeus, 1758), using a cellular level biomarker. The Neutral Red Retention Time (NRRT) assay was used to estimate effects at cellular levels. Significant effects were observed for the NRRT assay, even in low concentrations. The effects at cellular level were progressive, suggesting that the organisms are not capable to recover of such increasing effects. Additionally, the results show that the levels of LAS observed for Brazilian coastal waters may chronically affect the biota.
Keywords: Biomarkers; Detergent; Ecotoxicology; Effect; Marine pollution; Mussel